The effects of emotional intelligence, family environment and learning styles on social-science learning outcomes: An empirical analysis - Salamah; Purwaningsih; Jandra M.; Sentono T.; Huda M.; Maseleno A. (Mattingley Publishing, 2023)
Emotional intelligence; Students; Empirical analysis; Family environment; Indonesia; Junior high schools; Learning Style; Quantitative research; Sampling method; Science learning; Economic and social effects